Abnormal regulation of cytosolic calcium and pH in platelets of Sabra rats in early phases of salt hypertension development - Zicha, J; Kunes, J; Ben-Ishay, D; Devynck, M A (Canadian journal of physiology and pharmacology, 1996)
Platelet cytosolic free calcium concentration ([Ca2+]i) and pH (pHi) have been reported to be altered in both human essential and rat spontaneous hypertension. The aim of our study was not only to search for the occurrence of such alterations in platelets of rats with salt-induced hypertension but also to investigate whether these changes might precede blood pressure rise in this form of experimental hypertension. Using fluorescent probes fura-2 and BCECF, basal values and thrombin-induced changes of [Ca2+]i and pHi were determined in platelets of young hypertension-prone (SBH) and hypertension-resistant (SBN) Sabra rats fed either low-salt (0.3% NaCl) or high-salt (4% NaCl) diets. Under the conditions of low salt intake, basal [Ca2+]i values were similar in SBH and SBN rats, whereas pHi was significantly lower in SBH than in SBN animals. Thrombin induced smaller [Ca2+]i elevation but greater pHi rise in SBH rats compared with SBN animals. The initial rate of thrombin-induced Mn2+ entry, which reflects the opening of a particular subclass of thrombin-operated Ca2+ channels, was similar in both strains. The moderate hypertension elicited in SBH rats by high salt intake was not associated with major alterations of basal [Ca2+]i or pHi values. High salt diet feeding did not influence [Ca2+]i and pHi responses to thrombin in either strain. In contrast, high salt intake reduced thrombin-induced Mn2+ entry in SBN but not in SBH rats. Basal platelet [Ca2+]i values correlated positively with systolic but not with diastolic blood pressure. This could be ascribed to a very close relationship of basal [Ca2+]i values with pulse pressure. The abnormalities of [Ca2+]i and pHi handling in platelets of Sabra rats with salt-dependent genetic hypertension differ from those described in essential hypertensive patients or rat strains with spontaneous forms of genetic hypertension. Our study also indicated that alterations of platelet [Ca2+]i do not precede blood pressure elevation in salt hypertension.
Keywords: Calcium; Male; hypertenze; Rats, Inbred Strains; Sodium Chloride; vápník; Blood Platelets; Hydrogen-Ion Concentration; cytosol; mužské pohlaví; inbrední kmeny potkanů; Hypertension; chlorid sodný; Cytosol; koncentrace vodíkových iontů; krysa rodu Rattus; trombocyty; Animals; krevní tlak; zvířata; Rats; Blood Pressure